2019
DOI: 10.1108/jfep-05-2018-0075
|View full text |Cite
|
Sign up to set email alerts
|

The effect of corruption on FDI and its modes of entry

Abstract: Purpose The purpose of this paper is to empirically investigate the impact of corruption on foreign direct investment (FDI) and its two major modes of entry: greenfield investment (greenfield) and cross-border mergers and acquisitions (M&As). Design/methodology/approach Data are collected from 131 countries. Modern econometric techniques, including the generalized method of moments (GMM) estimator, two-stage least square estimator and two-step system GMM estimator, are used to evaluate the impact of corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 80 publications
(114 reference statements)
2
33
0
6
Order By: Relevance
“…Among the studies that employed GMM dynamic technique in their investigations of the link between corruption and FDI inflow are Aziz and Mishra (2015), Dauti (2015), Morrissey and Udomkerdmongkol (2012), Quazi, Vemuri and Soliman (2014), Kurul and Yalta (2017), Ajide and Raheem (2016), Yang et al (2018), Hayakawa, Kimuri andLee (2013), Helmy (2013), Lucke and Eichler (2016), Luu, Nguyen and Nam (2019). On their part, Castro and Nunes (2013), Mathur and Singh (2013), Quazi (2014), Subasat and Bellos (2013), Hossain (2016) and Bannaga et al (2013) deployed Generalized Least Squares (GLS) technique, whereas Fung and Gracia-Herrero (2012), Cuervo-Cazurra (2006), Júlio, Pinheiro-Alves and Tavares (2013) and Qian and Sandoval-Hernandez (2016) used Augmented Gravity Model (AGM) in their analysis.…”
Section: Corruption and Foreign Direct Investmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the studies that employed GMM dynamic technique in their investigations of the link between corruption and FDI inflow are Aziz and Mishra (2015), Dauti (2015), Morrissey and Udomkerdmongkol (2012), Quazi, Vemuri and Soliman (2014), Kurul and Yalta (2017), Ajide and Raheem (2016), Yang et al (2018), Hayakawa, Kimuri andLee (2013), Helmy (2013), Lucke and Eichler (2016), Luu, Nguyen and Nam (2019). On their part, Castro and Nunes (2013), Mathur and Singh (2013), Quazi (2014), Subasat and Bellos (2013), Hossain (2016) and Bannaga et al (2013) deployed Generalized Least Squares (GLS) technique, whereas Fung and Gracia-Herrero (2012), Cuervo-Cazurra (2006), Júlio, Pinheiro-Alves and Tavares (2013) and Qian and Sandoval-Hernandez (2016) used Augmented Gravity Model (AGM) in their analysis.…”
Section: Corruption and Foreign Direct Investmentmentioning
confidence: 99%
“…Arising from the contradictory outcomes from different studies using numerous methodologies in various contexts, some empirical works have employed different approach and frameworks by focusing on specific aspects of the relationships with a view to provide additional insights on corruption-FDI nexus (Luu et al, 2019). For example, Uhlenbruck et al (2006) and Smarzynska and Wei (2000) employed regression analysis in exploring the role of FDI ownership structure as foreign investors entry adjustment strategy in corrupt environments.…”
Section: Emerging Trendmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Gupta and Ahmed (2018) argue in the case of South Asian countries that corruption neither induces FDI nor impede corruption and conclude that corruption does not matter in case of FDI flows. Luu, Nguyen, Ho, and Nam (2018) concluded that the effect of corruption depending on the types of FDI and emphasized their conclusion by classifying FDI into green filed investment and cross-border mergers and acquisition whereas Burböck, Macek, Podhovnik, and Zirgoi (2018) found that a negative performance of corruption distance has not had a greater impact on FDI compared to the positive performance of corruption taking emerging and industrialized countries into consideration. Godinez and Garita (2015) have noted that firms in highly corrupted countries engaged in high corruption and vice versa whereas Ravi (2015) noted that the effect of corruption on FDI depends on nature, not by the size, and also found that corruption has an impact on FDI India but not in the case of China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Os impactos da corrupção ganharam destaque na área acadêmica, pois ela interfere em vários aspectos econômicos como os Investimentos Diretos Estrangeiros que o país recebe (Helmy, 2013;Petrou & Thanos, 2014;Luu, Nguyen, Ho, & Nam;, bem como provoca um impacto a nível institucional em relação às empresas (Wu, 2005;Tahoun, 2014), além de interferir em aspectos de gestão, como retenção de fluxo de caixa (Smith, 2016;Thakur & Kannadhasan, 2019), gerenciamento de resultados (Liu, 2016), entre outros, podendo, além disso, haver uma relação entre determinadas regiões do país e o envolvimento em atos de corrupção por parte das empresas (Cao, Qin, & Zhu, 2019).…”
Section: -Introduçãounclassified